TianGong database—an open-source, ILCD entry-level life cycle unit process database of china - Ming Xu; Weiqiang Chen; Yutao Wang; Lei Shi; Zhi Cao; Huimin Chang; Chang Chen; Xiangbin Ding; Jianwei Du; Huabo Duan; Kai Fang; Cuiyang Feng; et al. (Journal of Industrial Ecology, 2026)

Multi-core-shell MHS@PZS@Ni, Al-LDH: Synergistic flame retardancy and weather resistance enhancement for high-performance epoxy composites - Xiang Zeng; Guoqing Xiao; Haiqing Zhang; Rutong Song; Yuemei Zhang; Yue Fan; Shuyu Fu; Chunlin Chen; Chunyan Chen (Chemical Engineering Journal, 2026)

Transcriptomic and Physiological Insights into GA₃-Mediated Regulation of Fruit Abscission in Lonicera Caerulea L - Kailin Shao; Jing Chen; Bingbing Ren; Dong Qin; Xueting Wang; Chunlin Fu; Ran Gu; Jiacheng Li; Zhonglin Jia; Zhenyu Li; Junwei Huo; Huixin Gang (Journal of Plant Growth Regulation, 2026)

Analysis of cadmium sources in surface soil in typical karst regions: Anthropogenic input contribution and atmospheric transport impact - Zhe Liu; Guangyi Sun; Xian Wu; Weihai Yu; Heng Yao; Yu Lin; Chunlin Fu; Jinling Liu; Xinbin Feng (Journal of Hazardous Materials, 2026)

Carbon quantum dots from fallen leaves of Lonicera caerulea L.: An innovative plant growth promoter and fruit quality enhancer - Jiale Liu; Huixin Gang; Dong Qin; Haoyu Wang; Xueting Wang; Kailin Shao; Chunlin Fu; Jingjing Hong; Junwei Huo (Environmental Research, 2025)

LcMYB5, an R2R3-MYB family gene from Lonicera caerulea L., enhances drought and salt tolerance in transgenic tobacco and blue honeysuckle - Chunlin Fu; Chunyang Bian; Jing Chen; Qian Zhang; Dong Qin; Jiangkuo Li; Peng Zhang; Junwei Huo; Huixin Gang (Journal of Plant Physiology, 2025)

Transcriptomic and metabolomic analyses reveal molecular and metabolic regulation of anthocyanin biosynthesis in three varieties of currant - Haoyu Wang; Huixin Gang; Jing Chen; Jiale Liu; Xuelin Zhang; Chunlin Fu; Kailin Shao; Xueting Wang; Dong Qin; Junwei Huo (Food Research International, 2024)

Autotomy and Regeneration of Appendages in Crustaceans: A Review - Lei Liu; Dandan Tao; Chunlin Wang; Yuanyuan Fu; Sixiang Wang; Xinlian Huang; Wei Zhai; Weiwei Song (Journal of Ocean University of China, 2024)

Research and development factor mismatch, production losses, and energy efficiency: A study on Chinese regional economies - Changgao Cheng; Haiwei Zhou; Xiang Yan; Fu Xin; Qin Zhou; Chunlin Qian; Lidan Guo (Journal of Cleaner Production, 2024)

Mechanically robust, transparent, conductive hydrogels based on hydrogen bonding, ionic coordination interactions and electrostatic interactions for light-curing 3D printing - Sujuan Yan; Yian Chen; Dingfan Li; Yisi Zheng; Xuewei Fu; Baiqing Yu; Siyu Chen; Chunlin Ni; Haisong Qi; Wuyi Zhou (Chemical Engineering Journal, 2024)

Establishment of CRISPR-Cas-based antiparasitic agents for the swimming crab parasite Mesanophrys sp. - Xiaopeng Wang; Yueyue Zhou; Yingchao Zhang; Xiaofen Song; Ce Shi; Yuanyuan Fu; Lei Liu; Changkao Mu; Fei Yin; Weiwei Song; Chunlin Wang (Aquaculture, 2024)

Hg isotope evidence for oceanic oxygenation during the Cambrian Explosion - Haifeng Fan; Xuewu Fu; Ruofei Yang; Hanjie Wen; Chunlin Hu; Jack F. Ward; Hongjie Zhang; Hui Zhang; Xingliang Zhang (Geochimica et Cosmochimica Acta, 2023)

Variations of PM2.5-bound elements and their associated effects during long-distance transport of dust storms: Insights from multi-sites observations - Qingpeng Meng; Caiqing Yan; Ruiyu Li; Tianle Zhang; Mei Zheng; Yue Liu; Miao Zhang; Guixia Wang; Yuming Du; Chunlin Shang; Peng Fu (Science of The Total Environment, 2023)

Effects of different shelters on feeding, molting, survival, and growth of Scylla paramamosain - Dongping Zhou; Lei Liu; Xinlian Huang; Wei Fang; Yuanyuan Fu; Yuquan Li; Chunlin Wang (Frontiers in Marine Science, 2023)
Providing shelters is considered an effective method to prevent self-harm and improve the survival rate of Scylla paramamosain . In this study, four shelter groups—the shelters of which included fine sand, arched tiles, PVC pipes, and trapezoidal net cages—and one group without shelters were established to investigate the effects of shelters on S. paramamosain by calculating their feeding rate, molting rate, survival rate, and growth index. The results showed that the feeding rates of the fine sand and PVC pipe groups were greater than 12% and that the feeding rates of the arched tile and trapezoidal net cage groups were greater than 9%, while the feeding rate of the group without shelters was only 6.7%. The food conversion rates of both the fine sand and PVC pipe groups exceeded 21%. In contrast, the food conversion rate of the non-shelter group was the lowest at 14%. The molting rates of the fine sand and PVC pipe groups were the highest, reaching 29% in the later stages of the experiment, while the molting rate of the non-shelter group was only 19%. There was no significant difference in survival rates among the groups during the first 20 days of the experiment. However, on the 60th day, the survival rate of the fine sand group was 92%, while the non-shelter group had a survival rate of 79%. The experimental results showed that the incidence of cheliped injuries in the fine sand group was 16%, while it was 25% in the non-shelter group. During the daytime, the occupancy rate of burrows by the four shelter groups was 60–70%, while during the night, the occupancy rate of each shelter decreased to 40–50%, and there was no significant difference in occupancy rates among the shelter groups during the night. The weight and full carapace width of S. paramamosain in the fine sand and PVC pipe groups were significantly higher than those in the other groups ( P< 0.05), and the weight gain rate and specific growth rate of the fine sand and PVC pipe groups were significantly higher than those of the other groups ( P < 0.05). Research has shown that fine sand and PVC pipes, as shelters for S. paramamosain , can effectively prevent cannibalism, increase feeding rates and survival rates, and promote growth and molting. This study provides scientific guidance for the proper selection of shelters in the farming process of S. paramamosain .

Highly synergistic and polarized KNbO3/WO3 heterojunction for piezo-photocatalytic degradation of organic pollutant - Rui Huang; Wei Cai; Heng Zhang; Zhenhua Wang; Qin Zhang; Rongli Gao; Gang Chen; Xiaoling Deng; Xiang Lei; Jiling Dong; Xiaoyan Liu; Chunlin Fu (Journal of Environmental Chemical Engineering, 2023)

Comprehensive Genome-Wide Analysis of Wnt Gene Family and Expression Profiling during Limb Regeneration in Portunus trituberculatus - Yuanyuan Fu; Jie He; Lei Liu; Xinlian Huang; Yuankai Xu; Chunlin Wang (Fishes, 2022)
Wnt genes encode a family of secretory glycoproteins that are involved in various stages of organ development through regulation of cell proliferation, differentiation, and growth. Recently, Wnt genes have been shown to play an important role in regeneration processes. However, there have been no previous genome-wide analyses of the Wnt gene family members in crab species. In this study, a total of 13 Wnt family genes were identified from the genome of the swimming crab Portunus trituberculatus and classified into three main groups based on the conserved domain, protein sequence, and motifs. Chromosome location analysis showed that tandem duplication may have resulted in the expansion of the PtWnt gene family. RNA-seq results indicated that most PtWnt genes had a higher Fragments Per Kilobase of transcript sequences per Million base pairs (FPKM) value in the regenerating limb bud muscle than in the normal limb muscle, and the genes were enriched in a number of pathways that had biological functions underlying limb regeneration such as the cell surface receptor signaling pathway, the hippo signaling pathway, receptor binding, and basal cell carcinoma. Moreover, quantitative real-time PCR (RT-qPCR) analysis confirmed that the expression levels of nine PtWnts except for PtWnt1, PtWnt2, and PtWnt6 had a consistently increasing trend during limb regeneration. PtWnt1, PtWnt2, and PtWnt6 exhibited significantly up- or down-regulated expression at different limb regeneration stages. These results provide valuable information for further evolutionary and functional characterization of PtWnt genes and indicate the complexity and specialized mechanism of the Wnt signaling pathway regulating regeneration in crustaceans.

Fengyun-4 Geostationary Satellite-Based Solar Energy Nowcasting System and Its Application in North China - Chunlin Huang; Hongrong Shi; Ling Gao; Mengqi Liu; Qixiang Chen; Disong Fu; Shu Wang; Yuan Yuan; Xiang’ao Xia (Advances in Atmospheric Sciences, 2022)

Expression and function of WNT4 involved in larvae development and limb regeneration in Portunus trituberculatus - Zhiming Ren; Yuanyuan Fu; Lei Liu; Xiao Liu; Chunlin Wang (Journal of Oceanology and Limnology, 2021)

Inducible regulation of GDNF expression in human neural stem cells - ShuYan Wang; Ping Ren; YunQian Guan; ChunLin Zou; LinLin Fu; Yu Zhang (Science China Life Sciences, 2013)

Effects of temperature, starvation and photoperiod on otolith increments in larval Chinese sucker, Myxocyprinus asiaticus - Zhaobin Song; Zidong Fu; Chunlin He; Danzhou Shen; Bisong Yue (Environmental Biology of Fishes, 2009)

Otolith thermal marking in larval Chinese sucker, Myxocyprinus asiaticus - Zhaobin Song; Chunlin He; Zidong Fu; Danzhou Shen (Environmental Biology of Fishes, 2008)